1998
DOI: 10.1021/ac9705071
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Nuclear Magnetic Resonance Spectroscopy as a Probe For Reversed-Phase Liquid Chromatographic Bonded-Phase Solvation. 3. Tetrahydrofuran and Water Binary Systems

Abstract: Deuterium nuclear magnetic resonance ((2)H NMR) spectroscopy is a useful tool in probing molecular association between components in a binary hydro-organic mixture, such as tetrahydrofuran (THF) and water. Measurements of (2)H longitudinal relaxation times (T(1)) for deuterated analogs of THF and water provide this type of information, since the magnitude of T(1) is indicative of molecular association and mobility. This technique is also useful in determining the interactions between the mobile phase and rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These results are presented in Figure B and show a linear increase in the T 1 with temperature for all compositions investigated. There are 2 H T 1 studies of similar systems in the analytical literature, , but systematic errors or the effects of thermal convection on T 1 measurements are not discussed in these reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are presented in Figure B and show a linear increase in the T 1 with temperature for all compositions investigated. There are 2 H T 1 studies of similar systems in the analytical literature, , but systematic errors or the effects of thermal convection on T 1 measurements are not discussed in these reports.…”
Section: Resultsmentioning
confidence: 99%
“…Previous 2 H T 1 relaxation studies conducted examining common chromatographic solvent mixtures, such as CH 3 CN−H 2 O and CH 3 OH−H 2 O, both in the bulk solvent and in contact with stationary phases, led us to initially choose 2 H for our investigations. , We wanted to examine the 2 H T 1 relaxation times of CH 3 CN in CH 3 CN−H 2 O as a function of temperature and composition in an effort to validate the quadrupolar relaxation measurements as a means of determining changes in the solution viscosity. Our initial experiments indicated that there was not a simple relationship between the measured T 1 and η/ T .…”
mentioning
confidence: 99%
“…As the chains become more ordered, the partition of the solutes between the bonded layer and the mobile phase becomes entropically less favorable. Many experimental results support the assumption that the properties of the bonded alkyl chains change depending on the composition of the mobile phase (e.g., the volume of the bonded layer) and that these changes affect the retention behavior of the solutes [6,7]. A more detailed understanding of the effect of the composition of the mobile phase on the properties of the alkyl chains was afforded by the measurement of the equilibrium isotherms of various solutes on RPLC stationary phases [8].…”
Section: Introductionmentioning
confidence: 89%
“…Studies examining the properties of the mobile phase in the presence of numerous stationary phases have been conducted, and others have concentrated on investigating properties of the stationary phase under a wide array of thermodynamic conditions. Various spectroscopic methods including fluorescence, Raman, IR, UV−vis, small angle neutron scattering, sum frequency generation, , and NMR have been used to probe the mobile and stationary phases, as well as the composition, structure, and dynamics of the chromatographic interface. An underlying theme in a number of these works is the apparent reduction in the rate of molecular transport of the mobile phase system near the chromatographic interface. , , ,, The development of thermally stable stationary phases and high temperature RPLC techniques has made investigations of chromatographic interfaces at elevated temperatures increasingly important, and yet to date, the effects of temperature on the transport properties of the surface-affected mobile phase have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%